GUCY2C: at the intersection of obesity and cancer - Kim, Gilbert W. (2013)
Guanylyl cyclase C (GUCY2C) has canonical centrality in defense of key intestinal homeostatic mechanisms, encompassing fluid and electrolyte balance, epithelial dynamics, antitumorigenesis, and intestinal barrier function. Recent discoveries expand the homeostatic role of GUCY2C to reveal a novel gut-brain endocrine axis regulating appetite, anchored by hypothalamic GUCY2C which is responsive to intestine-derived uroguanylin. Thus, GUCY2C may represent a new target for anti-obesity pharmacotherapy. Moreover, the coincident regulation of energy balance and tumor suppression by a single hormone receptor system suggests that the GUCY2C axis might contribute to the established relationship between obesity and colorectal cancer. This confluence suggests that hormone supplementation to reconstitute GUCY2C signaling may be an elegant strategy to reverse both pathophysiologic processes.